2017
DOI: 10.1097/bpo.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Optimal Nail to Medullary Canal Diameter Ratio in Stainless Steel Flexible Intramedullary Nailing of Pediatric Femur Fractures

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…[8][9][10][11] Other recent studies have shown no correlation between canal fill and radiographic outcome. 5,12,13 The treatment failure group in our patient series had a significantly lower mean canal fill than the success group. Our ROC analysis identified 76% as the minimum optimal canal fill to prevent treatment failure, which closely matches the generally accepted recommen-dation of at least 80%.…”
Section: Discussionmentioning
confidence: 72%
“…[8][9][10][11] Other recent studies have shown no correlation between canal fill and radiographic outcome. 5,12,13 The treatment failure group in our patient series had a significantly lower mean canal fill than the success group. Our ROC analysis identified 76% as the minimum optimal canal fill to prevent treatment failure, which closely matches the generally accepted recommen-dation of at least 80%.…”
Section: Discussionmentioning
confidence: 72%
“… 19 The NCD ratio at the fracture level was calculated on both the anteroposterior (AP) and the lateral view. 36 Callus formation was assessed on AP and lateral view and the callus index was calculated as the maximum width of callus formation divided by the bone width at the same level ( Figure 3 ). 37 Fracture gap or overlap, and degree of horizontal fracture dislocation were assessed on the AP and the lateral view.…”
Section: Methodsmentioning
confidence: 99%
“…The first type is stainless steel Kirschner FIN without coating (Steel implant). Owing to their good mechanical properties, sufficient biocompatibility and relatively low cost steel FIN are used in clinical practice for the treatment of fractures and lengthening of long tubular bones in children [5,6].…”
Section: Methodsmentioning
confidence: 99%